Comparing the impacts of fossil and renewable energy investments in Indonesia: A simple general equilibrium analysis. Issue 6 (June 2020) - Hartono, Djoni; Hastuti, Sasmita Hastri; Halimatussadiah, Alin; Saraswati, Atina; Mita, Aria Farah; Indriani, Vitria
Abstract: Increasing electricity capacity to support economic growth has become a national development priority in Indonesia. The construction of a power plant needs to consider not only economic but also social and environmental impacts because the government can choose between fossil-based and renewable energy-based power plants. Thus, the decision to invest in a particular type of power plant technology must consider sustainability criteria. Using the social accounting matrix, this study aimed to simulate the impacts of an investment in a coal-fired power plant and compare those to the impacts of investments in renewable energy-based plants (geothermal, hydro, wind, and solar). The simulation results revealed that geothermal and wind power plants required the most significant investment and would increase the gross domestic product by 0.67% and 0.66%, respectively, representing the highest net value added to the economy compared to that of the other power plant options. The construction of a wind power plant promotes employment the most, by 0.70%. However, none of the power plant construction significantly affected income disparity. Additionally, compared to certain renewable power plants, a coal power plant might require less investment and have better employment and economic impacts. Nevertheless, its continuous emission effect from operation needs to be considered. Abstract : Energy; Economics; Inequality; Economic Development; Macroeconomics; Energy economics; Power Plant Investment; renewable energy; Social Accounting Matrix; Income Distribution; CO2 Emission